Figure S2 from Targeting MET and FGFR in Relapsed or Refractory Acute Myeloid Leukemia: Preclinical and Clinical Findings, and Signal Transduction Correlates - Evan C. Chen (15054014) (2025)
Merestinib and LY2874455 inhibit MET-activated signal transduction. A, AML cell lines treated with merestinib and LY2874455 in vitro for 1 hour exhibited decreased levels of pSTAT3 and pSTAT5 by phospho-flow cytometry. Standard errors are shown for KG1a (n=3) and HEL (n=2) cell lines. Representative flow cytometry histograms are shown in B. Reverse transcription-PCR showing decreased expression of CISH, a downstream target of STAT5, is displayed in C. Abbreviations: U = unstained; FGFRi = the FGFR inhibitor LY2874455.